A study on the effects of levamisole on the immune system of rainbow trout (Oncorhynchus mykiss, Walbaum) - Ispir, Ü; Dörücü, M (Tubitak Scientific & Technological Research Council Turkey, 2005)
The effects of levamisole on the specific and non-specific immune mechanisms of rainbow trout (Oncorhynchus mykiss, Walbaum) were examined. The weight of the 60 fish used (30 in the control group and 30 in the experimental group) in this study was 99.4-216.0 g. After injecting 5 mg kg(-1) of levamisole intraperitonally, blood was taken from the heart of 30 anesthetized fish and hematocrit, leucocrit, leucocyte level, glass-adherent Nitroblue tetrazolium (NBT) positive cell activation, NBT activities, phagocytic activity, potential killing activities of neutrophyl and monocytes, myeloperoxidase production (MPO), immunoglobulin, lysozyme and ceruloplasmin (Cp) activity were determined on days 3, 7, 10 and 14. The same procedure was conducted on a control group. No differences were found in the levels of hematocrit, leucocrit or immunuglobulin between the control and experimental groups (P > 0.05). However, there were considerable increases in the other immune parameters and significant differences were detected between the control and experimental groups (P < 0.05, P < 0.01, P < 0.001).
Keywords: immunomodulation; immunity; levamisole; rainbow trout